Writing Unleashed Content and Structure - Priebe, Sybil; Marman, Ronda; Anderson, Dana; Open Textbook Library (Open Textbook Library, 2019)
Welcome to Writing Unleashed, designed for use as a textbook in first-year college composition programs, written as an extremely brief guide for students, jam-packed with teachers' voices, students' voices, and engineered for fun.
THE STARTING POINT -- CONTENT AND STRUCTURE -- STRATEGIES AND MODES -- GENRES -- THE WRITING PROCESS -- RESEARCH UNIT -- NERD UNIT
In English.
Description based on print resource
Keywords: Communication -- Textbooks; Humanities -- Textbooks; Rhetoric -- Textbooks